Media infrastructures and the politics of digital time : essays on hardwired temporalities - Volmar, Axel; Stine, Kyle (Recursions: theories of media, materiality, and cultural techniques., 2021)
In a crucial sense, all machines are time machines. The essays in 'Media Infrastructures and the Politics of Digital Time' develop the central concept of hardwired temporalities to consider how technical networks hardwire and rewire patterns of time. Digital media introduce new temporal patterns in their features of instant communication, synchronous collaboration, intricate time management, and continually improved speed. They construct temporal infrastructures that affect the rhythms of lived experience and shape social relations and practices of cooperation. Interdisciplinary in method and international in scope, the volume draws together insights from media and communication studies, cultural studies, and science and technology studies while staging an important encounter between two distinct approaches to the temporal patterning of media infrastructures, a North American strain emphasizing the social and cultural experiences of lived time and a European tradition, prominent especially in Germany, focusing on technological time and time-critical processes.